Construction of cellulose-degrading microbial consortium and evaluation of their ability to degrade spent mushroom substrate - Long, Junqiao; Wang, Xueli; Qiu, Shuyi; Zhou, Wei; Zhou, Shaoqi; Shen, Kaiwei; Xie, Lili; Ma, Xiao; Zhang, Xuyi (Frontiers in Microbiology, 2024)
Spent mushroom substrate (SMS) is a solid waste in agricultural production that contains abundant lignocellulosic fibers. The isolation and screening of microorganisms with a high cellulase degradation ability is key to improving the utilization rate of SMS. In this study, four strains with high cellulase activity were isolated and screened from SMS samples. Based on antagonistic tests and enzyme activity tests, cellulose-degrading microbial consortiums PX1+F7 and F16+F were constructed, then SMS was used as the carbon source, their Carboxymethyl Cellulase (CMCase) activities are 225.16 and 156.63 U/mL and filter paper enzyme (FPase) activities are 1.91 and 1.64 U/mL, respectively. The identified strains F16, F, and F7 were all Bacillus amyloliquefaciens, while strain PX1 was Bacillus velezensis，based on sequences of their 16S rRNA, gyrA genes. The study found that PX1+F7 had the highest degradation rates of hemicellulose and lignin in SMS, reaching 52.96% and 2 52.13%, respectively. Meanwhile, F16+F had a cellulose degradation rate of up to 56.30% in the SMS. Field emission scanning electron microscopy (FESEM) analysis showed significant changes in the surface microstructure of SMS after treatment with the microbial consortium, indicating the effective degradation of SMS by the strains. The changes in absorption peaks observed in Fourier transform infrared spectroscopy (FTIR) and the increase in crystallinity observed in X-ray diffraction (XRD) confirmed the actual degradation effect of the microbial consortium on SMS. The results of the study indicate that PX1+F7 and F16+F can effectively secrete cellulase and degrade cellulose, which has practical significance in the degradation of SMS.